Teachers' Perception of The Implementation of Pilot Teacher Training on EMI - Hariyanti, Yuni (JOLLT Journal of Languages and Language Teaching, 2023)
As teachers are an essential element in education, there is always a need to improve their skills from time to time. The training that teachers get varies, depending on the need of the teachers themselves or the institution they work for. In Al-Hasra Foundation, there is a need for internationalizing the institution so the teachers were equipped with training on EMI (English as a Medium of Instruction). This training was the first training conducted to meet the internalization need of the institution. Therefore, this study was aimed at knowing the perception the teachers have towards the first implementation of the training. The result of this research is beneficial for both the teachers and the institution because the teachers' perception will affect the success of the training itself for both sides. Fifteen non-English teachers of Al Hasra foundation joined the teacher training. The data of this research were taken from the questionnaires and the classroom observation. The results of the questionnaires were analyzed to get the percentage while the classroom observation was analyzed to enrich the findings. The result showed that teachers of Al-Hasra Foundation performed a positive perception towards the pilot teacher training on EMI by demonstrating that the training has improved their knowledge of the use of English in a classroom context, and it has increased their motivation and self-confidence in conducting the teaching activity in English.